STRATEGI PENGGUNAAN MULTIMEDIA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TINGKAT SEKOLAH DASAR - Sulistiawati, Esti; Abidin, Jaenal (Universitas Islam Madura, 2024)
In the current context, learning media has a significant role in helping convey messages and information (learning materials) to students, this is because learning is essentially the process of conveying messages and information from educators to students which can be realized through interactive and dialogic activities in life. daily. This article aims to analyze strategies for using multimedia in Islamic religious education learning at the elementary school level. The research method used is a qualitative method with data collection through literature study. The results of the research show that the use of multimedia in the form of interactive animation or animated videos in Islamic learning at the elementary school level can effectively make it easier for students to understand lessons, be more enjoyable, and can increase the activeness and enthusiasm for learning of elementary school students. This is because multimedia is one of the main elements in the learning process which can be a means for teachers to create a maximum, effective and efficient learning process. Thus, the teacher's role is very necessary to choose learning strategies that suit the type and learning style of elementary school students. The implications of this research activity are: 1) increasing the effectiveness of PAI learning, 2) curriculum development, 3) providing varied learning resources, 4) implementing training for PAI teachers.